Allosteric interactions of DNA and nucleotides with S. cerevisiae RSC - Malik, Shuja Shafi (2011)
RSC, Remodel the Structure of Chromatin, is an essential chromatin remodeler of Saccharomyces cerevisiae that has been shown to have DNA translocase properties. We studied the DNA binding properties of a ‘trimeric minimal RSC’ (RSCt) of the RSC chromatin remodeling complex and the effect of nucleotides on this interaction using fluorescence anisotropy. RSCt binds to 20 bp fluorescein labeled double stranded DNA with a K(d) of approximately 100 nM. The affinity of RSCt for DNA is reduced in the presence of AMP-PNP and ADP in a concentration dependent manner with the addition of AMP-PNP having the more pronounced effect. These differences in the magnitude at which the binding of ADP and AMP-PNP affect the affinity of DNA binding by RSCt suggests that the physical movement of the enzyme along DNA begins between the binding of ATP and its subsequent hydrolysis. Furthermore, the fact that the highest affinity for DNA binding by RSCt occurs in the absence of bound nucleotide offers a mechanistic explanation for the low apparent processivity of DNA translocation by the enzyme.